Building permanently optically active particles from an absolutely achiral polymer. Issue 14 (23rd March 2022) - He, Zixiang; Miao, Tengfei; Cheng, Xiaoxiao; Ma, Haotian; Ma, Yafei; Zhang, Wei; Zhu, Xiulin
Abstract : A novel strategy has developed for constructing polymer particles with permanent chirality by partially cross-linking the azobenzene units to allow perfect recovery of the destroyed helical superstructure without any chiral sources. Abstract : Chirality in polymer particles represents one of the most dynamic areas of nanoscale materials today. The chirality of most chiral polymeric particles (CPPs) derived from achiral monomers/polymers has a strong dependence on the chiral source. After the removal of the chiral source, the helical structures in these CPPs cannot be recovered from external-stimuli-triggered destruction. Herein, for the first time, a novel strategy has developed for constructing polymer particles with permanent chirality by partially cross-linking the azobenzene (Azo) units to allow perfect recovery of the destroyed helical superstructure without any chiral sources. A fraction of the Azo units was modified with hydroxyl groups as cross-linking sites to permanently store the chiral information from the chiral solvent in the CPPs. Remarkably, the stored chiral information by the fraction of cross-linked Azo units can trigger the other free Azo units to reconstruct the helical superstructure to the previous level by simple heating–cooling treatment or visible light irradiation. We anticipate that our strategy will promote the flexible design and fabrication of new types of advanced functional chiral nanomaterials from absolute achiral sources.